Implementasi Scan QR Code Pada Sistem Donasi Anak Yatim Berbasis Mobile Menggunakan Metode Extreme Programming Studi Kasus : Yayasan Amal Khair Yasmin - Yoga Dwi Martin; Ita Handayani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Yayasan Amal Khair Yasmin experiencing problems, namely the problems faced by the institution in finding new donors to the extent of distributing brochures or word of mouth and the limited space or container to inform and inform the public that the institution needs assistance and there are still errors in recording donations from donors in the form of money or goods. . By using mobile-based donation application media, and the existence of internet technology and quick responses code (QR Code) and currently donations can be made online, in building a mobile-based orphan donation system using the Extreme Programming (XP) method and can make it easier for donors to receive donations. make donations, and obtain information from the foundation.